Some Exact Results on Lindley Process with Laplace Jumps - Emanuele Lucrezia; Laura Sacerdote; Cristina Zucca (Mathematics)
We consider a Lindley process with Laplace-distributed space increments. We obtain closed-form recursive expressions for the density function of the position of the process and for its first exit time distribution from the domain <semantics>[0,h]</semantics>. We illustrate the results in terms of the parameters of the process. An example of the application of the analytical results is discussed in the framework of the CUSUM method.